Effect of informative claims on the attitude of Italian consumers towards cultured meat and relationship among variables used in an explicit approach. (January 2022) - Piochi, Maria; Micheloni, Matteo; Torri, Luisa
Graphical abstract: Highlights: The efficacy of different informative claims about cultured meat was assessed. Claims referred to human safety, animal welfare, and environmental impact. Claims significantly increased favour, and willingness to substitute cultured meat. Human safety and animal welfare were the most divisive claims across sex and age. Willingness to try cultured meat correlated modestly with willingness to substitute. Abstract: Cultured meat (CM) is a potential sustainable novel food. Consumers' attitude towards this product is currently under investigation but a direct comparison of the effect of different types of information on consumers' response to CM is lacking. This study aimed: 1. to compare the efficacy of different informative claims in improving attitude towards CM; 2. to verify the effect of previously studied variables on attitude towards CM. Four information types were compared (human safety; animal welfare; environmental impact; no additional information: control), each envisaging two additional claims ('Antibiotic-free' and 'Pathogen- and zoonosis-free' for human safety; 'No animal breeding' and 'No animal slaughtering' for animal welfare; '82–96% reduction of water consumption' and '99% reduction of soil usage' for environmental impact). The response variables were favour towards CM, willingness to try, willingness to purchase, and willingness to substitute traditional meat with CM. Data from 603 participants (61% females, 15–80 years old) randomly assigned to four blocks, each corresponding to one type of information, were analysed. Participants were uniform among blocks in terms of socio-demographic data, frequency of consumption of traditional meat, previous knowledge of CM, food neophobia, and disgust sensitivity. The type of information given to respondents improved favour and willingness to substitute compared to the control, without differences across blocks. The effects of the additional claims were comparable. Environmental claims unified respondents, while human safety and animal welfare claims were divisive for sex and age groups. Favour, willingness to try, willingness to purchase, and willingness to substitute were positively correlated ( r 0.38–0.72) but the weak correlation between willingness to try and willingness to substitute indicates that being curious may not imply the modification of actual behaviour (traditional meat substitution). Response variables seemed not to be interchangeable. Females showed higher willingness to substitute CM to conventional meat if informed with claims related to human safety. Youngsters (under '30 years old), who are plausibly the real future target, showed higher favour towards CM if provided with information related to animal welfare and human safety. Production companies should carefully choose what additional information to provide, depending on the consumer target.